Effects of Human Mesenchymal Stem Cells Isolated from Wharton's Jelly of the Umbilical Cord and Conditioned Media on Skeletal Muscle Regeneration Using a Myectomy Model - T. Pereira; P. A. S. Armada-da Silva; I. Amorim; A. Rêma; A. R. Caseiro; A. Gärtner; M. Rodrigues; M. A. Lopes; P. J. Bártolo; J. D. Santos; A. L. Luís; A. C. Maurício (Hindawi Limited, 2014)
Skeletal muscle has good regenerative capacity, but the extent of muscle injury and the developed fibrosis might prevent complete regeneration. The in vivo application of human mesenchymal stem cells (HMSCs) of the umbilical cord and the conditioned media (CM) where the HMSCs were cultured and expanded, associated with different vehicles to induce muscle regeneration, was evaluated in a rat myectomy model. Two commercially available vehicles and a spherical hydrogel developed by our research group were used. The treated groups obtained interesting results in terms of muscle regeneration, both in the histological and in the functional assessments. A less evident scar tissue, demonstrated by collagen type I quantification, was present in the muscles treated with HMSCs or their CM. In terms of the histological evaluation performed by ISO 10993-6 scoring, it was observed that HMSCs apparently have a long-term negative effect, since the groups treated with CM presented better scores. CM could be considered an alternative to the in vivo transplantation of these cells, as it can benefit from the local tissue response to secreted molecules with similar results in terms of muscular regeneration. Searching for an optimal vehicle might be the key point in the future of skeletal muscle tissue engineering.